Review of Cassin, B. Quand dire, c’est vraiment faire. Homère, Gorgias et le peuple arc-en-ciel (2018) - Cardim, Leandro (Revista Archai, 2022)
Review of Cassin, B. Quand dire, c’est vraiment faire. Homère, Gorgias et le peuple arc-en-ciel(2018)